Encouraging sustainable environment using bicycle sharing system in University Campus, Bangkok / Jin Hai Yan. - Jin, Hai Yan (Universiti Teknologi MARA, Shah Alam: Faculty of Architecture, Planning and Surveying, 2020)
Chulalongkorn University (CU) is the oldest university in Thailand. In the campus, it provides various environmentally friendly transportation modes such as shuttle buses, EV sharing vehicles, bicycles, and cover way for walking. Students today need convenient and fast commuting in the campus. As a new emerging way for students using, bike-sharing system (BSS) has been provided in the campus since 2014. However, the BSS in CU is still not so efficient and unpopular. This research aims to find out how to encourage the use of on-campus BSS in CU by using various research methods including interview, questionnaires and observation plans, and the researcher own experiences on using BSS in the campus. The survey results indicate that only 2% used bicycle for traveling from accommodation to the university; the most popular transportation mode was MRT/BTS, followed by public bus for graduate students, and by walking for undergraduate students. This implies that most of the respondents preferred public transportation rather than using their own cars or motorcycles. Upon questions about the preferring on-campus transportation modes, it was found that nearly half preferred using shuttle bus, followed by walking, while only 2.4% prefer using BSS. The university should raise awareness of the students to realize advantages of the BSS and providing more opportunities for students to know the bike-sharing system. Then, the university should improve the quality of the sharing bikes and motivate more students to use the system.